A Single Sample Method for Estimating Glomerular Filtration Rate in Cats. (6th May 2013) - Finch, N.C.; Heiene, R.; Elliott, J.; Syme, H.M.; Peters, A.M.
<x xml:space="preserve">Abstract</x> Background Validated methods of estimating glomerular filtration rate (GFR) in cats requiring only a limited number of samples are desirable. Hypothesis/Objectives To test a single sample method of determining GFR in cats. Animals The validation population (group 1) consisted of 89 client‐owned cats (73 nonazotemic and 16 azotemic). A separate population of 18 healthy nonazotemic cats (group 2) was used to test the methods. Methods Glomerular filtration rate was determined in group 1 using corrected slope‐intercept iohexol clearance. Single sample clearance was determined using the Jacobsson and modified Jacobsson methods and validated against slope‐intercept clearance. Extracellular fluid volume (ECFV) was determined from slope‐intercept clearance with correction for the 1 compartment assumption and by deriving a prediction formula for ECFV (ECFVPredicted) based on the body weight. The optimal single sample method was tested in group 2. Results A blood sample at 180 minutes and ECFVPredicted were optimal for single sample clearance. Mean ± SD GFR in group 1 determined using the Jacobsson and modified Jacobsson formulae was 1.78 ± 0.70 and 1.65 ± 0.60 mL/min/kg, respectively. When tested in group 2, the Jacobsson method overestimated multisample clearance. The modified Jacobsson method (mean ± SD 2.22 ± 0.34 mL/min/kg) was in agreement with multisample clearance (mean ± SD 2.19 ± 0.34 mL/min/kg). Conclusions and Clinical Importance The modified Jacobsson method provides accurate estimation of iohexol clearance in cats, from a single sample collected at 180 minutes postinjection and using a formula based on the body weight to predict ECFV. Further validation of the formula in patients with very high or very low GFR is required.